From third cinema to the video movement: Theories and decolonizing practices in latinamerican audiovisual materials - de la Fuente, Alejandro; Guerrero, Claudio (Nawi, 2021)
The present text approaches the Latin American audiovisual space in different historical contexts represented by two different groups and mediums, on the one hand, the third cinema in the 60s and 70s and, on the other hand, the Latin American Video Movement in the 80s and 90s. The objective is to analyze the decolonizing potential of the theories and practices registered in them. To do so, we review their developments, continuities and projections, focusing on the way in which the Latin American colonial condition was conceived, the methodologies and strategies that nurtured their decolonizing audiovisual practices and the ways in which they sought autonomy in the production, distribution and reception of audiovisuals. Finally, we put both moments and groups in perspective to account for their points of encounter and tension.